2018
DOI: 10.1155/2018/4950705
|View full text |Cite
|
Sign up to set email alerts
|

Di‐2‐pyridylhydrazone Dithiocarbamate Butyric Acid Ester Exerted Its Proliferative Inhibition against Gastric Cell via ROS‐Mediated Apoptosis and Autophagy

Abstract: Diversified biological activities of dithiocarbamates have attracted widespread attention; improving their feature or exploring their potent action of mechanism is a hot topic in medicinal research. Herein, we presented a study on synthesis and investigation of a novel dithiocarbamate, DpdtbA (di-2-pyridylhydrazone dithiocarbamate butyric acid ester), on antitumor activity. The growth inhibition assay revealed that DpdtbA had important antitumor activity for gastric cancer (GC) cell lines (IC50 = 4.2 ± 0.52 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…To extend our knowledge for the dithiocarbamate derivative, the effect of DpdtbA on the proliferation of esophageal cancer cell lines was further investigated. Interestingly, the DpdtbA-induced growth inhibition involved p53 depletion, which was not consistent with that reported previously in gastric cancer cell lines [24]. Additional investigations revealed that the p53 degradation was through chaperon-mediated autophagy rather than MDM2-mediated ubiquitination.…”
Section: Introductioncontrasting
confidence: 59%
See 3 more Smart Citations
“…To extend our knowledge for the dithiocarbamate derivative, the effect of DpdtbA on the proliferation of esophageal cancer cell lines was further investigated. Interestingly, the DpdtbA-induced growth inhibition involved p53 depletion, which was not consistent with that reported previously in gastric cancer cell lines [24]. Additional investigations revealed that the p53 degradation was through chaperon-mediated autophagy rather than MDM2-mediated ubiquitination.…”
Section: Introductioncontrasting
confidence: 59%
“…As shown in Figure 2, DpdtbA caused an accumulation of the ESC cells in the S phase for both cell lines, and the percentages at the S phase significantly increased by 10 to 17% during 24 h insult of the agent, thereby decreasing the proportion of cells in the G1 phase. Those indicated that DpdtbA could disturb cell cycle and arrest the cells at the S phase, which was not consistent with that in gastric cell lines [24], indicating that DpdtbA-induced cell cycle delay was cell line dependent. Furthermore, it was well documented that the progression of cells is regulated by cyclins and CDK (cyclin-dependent kinase) proteins, and cyclin A and CDK2 are known to play an important role in the regulation of DNA synthesis during cell-cycle progression at the S phase; thus, the expression of CDK2 in different conditions was determined.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Cells were seeded into a 6-well plate and treated as described above for the cell viability assay. The cells were treated with either the agent alone (1.0 or 2.0 μ M) or a combination with 3-MA (1.5 mM) or NAC (1.5 mM)) for 24 h. Then, the cell culture was removed, following PBS washing, trypsin digestion; finally, the MDC (50 μM) were added as described previously [ 47 ]. The stained cells were subjected to flow cytometric analysis (Becton-Dickinson, USA).…”
Section: Methodsmentioning
confidence: 99%